Interactions of nutrient and water availability control growth and diversity effects in a Salix two‐species mixture. Issue 5 (18th January 2022) - Lindh, Magnus; Hoeber, Stefanie; Weih, Martin; Manzoni, Stefano
Abstract: Plant growth is constrained by resource availability and interactions among limiting resources—abundance in one resource (e.g., nutrients) might promote growth, thereby causing the depletion of other resources (e.g., water), potentially inducing stress or mortality. In a diverse plant community, complementary resource use has been hypothesized to increase the overall productivity, but how diversity effects vary with interacting water and nutrient limitation and through time is not known. Here, we address this knowledge gap in a controlled pot experiment where species composition (two Salix species in monoculture or mixture), nutrient addition, and watering frequency (for fixed total water inputs) were varied during two growing seasons. High nutrient availability promoted plant growth and nitrogen accumulation at the pot scale, as well as increased allocation aboveground, but also triggered more intense water stress and mortality, as larger plants depleted soil water during warm periods. Supplying water more frequently slightly alleviated water stress under high nutrient availability, thus promoting growth and nitrogen accumulation. The species mixtures performed better than the average of the mixture constituents (positive net diversity effects) and increasingly so through time. The complementarity and selection effects, respectively, increased and decreased under both high nutrient availability and high watering frequency. Overall, these results suggest that as plants grow larger, plant interactions and resource partitioning intensify, causing the positive diversity effects, but also that drought consequences might be exacerbated in plant communities rapidly growing thanks to high nutrient supply.